Shifts in Endogamy Tradition within Arab-Indonesian Populations: A Study on an Alawiyyin Family in Bekasi, West Java - Alaydrus, Sayf Muhammad (Faculty of Social Science, Universitas Negeri Semarang, 2023)
Ethnicity-based endogamous marriage is often related to the cultures of Arab descent in Indonesia. These past decades, sociocultural changes affected several cultures across Indonesia, mainly due to the rapid growth of information access and scientific knowledge. These changes also occurred within the Arab-descent communities in Indonesia, including changes in value and practice in their marriage tradition. This ethnographic research attempted to reexplore, redefine, and reinterpret the current perspectives of endogamous marriage through the minds of an Alawiyyin family in Bekasi, West Java. The informants mentioned that endogamous marriage was deemed irrelevant since 30-40 years ago, and what was once the norm changed into a simple preference. This change happened because of the elders’ and family patriarchs’ open-mindedness, and thus, nurtured a more welcoming attitude toward non-Arabs and non-Alawiyyins. They also realized that forced endogamy oftentimes caused feelings of solitude and discomfort to those affected. To prevent such discrimination from happening again, the informants mentioned that they grant more freedom to their offspring to select their own life partner, even though parental approval is still important to the couple’s marriage.